Wallace Thurman’s Marginality and his Quest for Recognition through Primitivism: A Critical Analysis of his Play Harlem - Farshid Nowrouzi Roshnavand, Dr. Maryam Soltan Beyad (Journal of Research in Humanities, 2023)
From the beginning of their presence in the United States, blacks faced an all-encompassing process of marginalization and inferiorization imposed by the dominant white America, so they had to adopt different kinds of strategies in order to fight marginalization and find the respect and recognition they longed for. In the 1920s, young African American writers, greatly influenced by the modernist primitivism of the post-war Europe and the hedonistic zeitgeist of the Jazz Age America, opted to give a primitive, exotic portrait of Negro life. They naïvely believed that their primitivist representational strategy could prove their unique features and worth to whites and thus could bring them a more secure status in society by fascinating the post-war disillusioned Americans. Wallace Thurman was one of these writers who was extremely marginalized because he was not only black, but also homosexual. Trying to dispose of his subalternized status in society, Thurman went for a decadent, primitivist representational strategy since he held that an exotic portrait of Negro life, which catered to the taste of dominant whites, could grant him recognition and respect of which he had been deprived due to his “non-normative” skin color and sexual orientation. This paper tries to analyze Thurman’s marginality and its influence on his choice of primitivism through a critical analysis of his play Harlem. It also aims to show that Thurman’s goal to achieve recognition through the exotic representation of Negro life was a naïve, simplistic agenda which never materialized